Non-surgical and non-pharmacological interventions for congenital muscular torticollis in the 0-5 year age group - Antares, J.; Jones, M.; King, J.; Chen, T.; Lee, Crystal; Macintyre, S.; Urquhart, D. (John Wiley & Sons, Ltd., 2018)
© 2018 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the comparative effectiveness of non-surgical and non-pharmacological interventions for the management of congenital muscular torticollis (CMT) in infants and children aged 0 to 5 years.